(untitled) (London, 1988)
This book focuses the problems of food preservation in tropical region and the means for their amelioration by control of the internal aqueous environment. It is divided into three sections, the first of which reviews in detail the fundamental aspects concerning the physio-chemical condition of water in foods and its influence on biological, chemical and physical changes. The subsequent two sections deal with practical studies on the preservation of foods by moisture control in various parts of the tropics, with particular reference to South East Asia. Section 2 deals with food commodities of animal origin, whilst Section 3 deals with those of plant origin
Keywords: Food; Preservation